EVALUATION OF TERMITICIDAL PROPERTIES OF CHEMICALLY MODIFIED CASHEW NUT SHELL LIQUID - Eliveha, ObegeEdgar (My University, 2015)
Cashewnutshellliquid(CNSL),aby-productcashewnutprocessing contains:anarcardicacid,cardanol,cardol&2–methylcardol. •Cardanol&cardolwereisolatedfromCNSLusingchemicalmethod adoptedfromKumar(2002). •Preservativewaspreparedbyincorporatingcopper&chlorineinCNSL, decarboxylatedCNSL,cardanol&cardol.itsefficacyagainsttermiteswas comparedwithcommerciallyavailabletermiticide(chlorpyrifos) •Testsampleswerecoatedwithpreservativesformulated,anotherbatch chlorpyrifos&controlbeingwoodblocksdippedindistilledwaterthen introducedatanthillshavinganestofMicrocerotermesbeesonifor60 days. •Keenobservationsweremadeonfeedinghabitsoftermitesonwood samplesofJuniperusprocera,Grevilearobusta,&Pinusinsularis. •%weightlosswascalculatedforeachblockaftertermiteexposure&knife testcarriedouttodeterminetheextentofdestruction.
Keywords: EVALUATION OF TERMITICIDAL PROPERTIES